Coarse Grained Molecular Dynamics Simulation of Interaction Between Hemagglutinin Fusion Peptides and Lipid Bilayer Membranes (Advances in Applied Mathematics and Mechanics, 2019)
Microscopic level interaction between fusion-peptides and lipid bilayer membranes plays a crucial role in membrane fusion, a key step of viral infection. In this paper, we use coarse-grainedmolecular dynamics (CGMD) simulations to study the interactionbetween hemagglutinin fusion-peptides and phospholipid bilayermembranes. With CGMD, we are able to simulate the interaction offusion peptides with a relatively large piece of membrane for asufficiently long time period, which is necessary for a detailedunderstanding of the fusion process. A conformation of the peptidewith a kink at the level of phosphate group is obtained, consistentwith NMR and EPR studies. Our results show that the N-terminalsegment of the peptide inserts more deeply into the membrane bilayercompared to the C-terminal segment, as observed in previousexperiments. Our simulations also show that the presence of fusionpeptides inside the membrane may cause bilayer thinning and lipidmolecule disorder. Finally, our results reveal that peptides tend toaggregate, indicating cluster formation as seen in manyexperiments.